Фильтрация шумов в тепловой дефектоскопии при контроле трубопроводов - Куликов, Д. И. (ХНУРЕ, 2019)
The possibility of thermographic method application to the estimation of gas-main pipeline liquid phase contamination content level is considered. The environment temperature effect on the considered method sensitivity is ana-lyzed.